Relationship of neuropathic pain component and osteoarthritis stage in patients with knee osteoarthritis (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine the frequency of neuropathic pain (NP) in patients with knee osteoarthritis (OA) and the relationship between knee OA stage and NP degree.Materials and Methods: This study included 63 patients (11 male, 52 female; mean age 62.4 ± 11.9 years; range 40-89 years) who were diagnosed with knee OA according to the American College of Rheumatology between January and May 2019. For all the participants, the knee pain was evaluated with the Visual Analog Scale (VAS), the functional evaluation was performed through Western Ontario and McMaster University (WOMAC) Osteoarthritis Index, and the neuropathic pain (NP) component was evaluated through Pain-DETECT Questionnaire (PDQ). The Kellgren-Lawrence grading system was used to determine radiological severity.Results: Of the total, 18 patients (28.5%) were classified as possible NP and 15 patients (23.5 %) were classified as likely NP. The symptom durations of the patients with final NP diagnosis were longer (p
Keywords: Knee osteoarthritis; neuropathic pain